STRESS ANALYTICS OF MEDICAL STUDENTS AT FACULTY OF MEDICINE UNIVERSITY OF SURABAYA - Sajuni Widjaja; Agus Cahyono (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Stress is a mental response of a person's body that arises as a reaction to external demands that are considered dangerous or threatening him / her. Various studies have shown that stress on students especially on medical students is very high. This study specifically aimed to analyze the level of stress in preclinical students level 1, 2 and 3 of the Faculty of Medicine, University of Surabaya. Case discussion : This research is an analytic survey with a cross-sectional study approach. Data were collected through the Medical Student Stressor Questionnaire (MSSQ). A total of 114 medical students were obtained, consisting of 85 female students and 29 male students. Number of class 2017 are 38 medical students, number of class 2018 are 37 medical students, and class 2019 are 39 medical students. A total of 94 medical students live with their parents but the remaining 20 medical students do not live with their parents. Stressors in this study consisted of six groups, namely academic-related stressors (ARS), intrapersonal and interpersonal related stressors (IRS), teaching and learning related stressors(TLRS), social related stressors (SRS), drive and desire related stressors (DRS), group activities related stressors (GARS).Conclusion: It was found that the most stressors were academic-related stressors. Women are generally more stressed than men in drive and desire related stressors. There were no different stress between medical students who live and not live with their parents.